Adoptive T cell therapy for solid tumors: current landscape and future challenges - Albarrán, Víctor; San Román, María; Pozas, Javier; Chamorro, Jesús; Rosero, Diana Isabel; Guerrero, Patricia; Calvo, Juan Carlos; González, Carlos; García de Quevedo, Coral; Pérez de Aguado, Patricia; Moreno, Jaime; Cortés, Alfonso; et al. (Frontiers in Immunology, 2024)
malignancies have launched the investigation of ACT in patients with refractory solid malignancies. However, certain characteristics of solid tumors, such as their antigenic heterogeneity and immunosuppressive microenvironment, hamper the efficacy of antigen-targeted treatments. Other ACT modalities, such as TIL therapy, have emerged as promising new strategies. TIL therapy has shown safety and promising activity in certain immunogenic cancers, mainly advanced melanoma, with an exciting rationale for its combination with immune checkpoint inhibitors. However, the implementation of TIL therapy in clinical practice is hindered by several biological, logistic, and economic challenges. In this review, we aim to summarize the current knowledge, available clinical results, and potential areas of future research regarding the use of T cell therapy in patients with solid tumors.Con formato: Inglés (americano) Eliminado: ¶ 92 Con formato: Inglés (americano) Con formato: Inglés (americano) Con formato: Inglés (americano) Con formato: Inglés (americano) Con formato: Inglés (americano) Con formato: Inglés (americano) Con formato: Inglés (americano) Con formato: Inglés (americano) Con formato: Inglés (americano) Con formato: Inglés (americano) Con formato: Inglés (americano) Con formato: Inglés (americano) Eliminado: ¶ 93 Eliminado: <#>Immunotherapy beyond immune checkpoint 94 inhibitors ¶ 95 ¶ 96 Con formato: Inglés (americano) Con formato: Inglés (americano) Eliminado: , often in combination with IL2 as an immune activator 97 Con formato: Normal, Justificado